Emerging Needs of Wetlands Protection for the Conservation of Wild Rice Biodiversity in Nepal: A Case Study from Lumbini Area - Siwakoti, Mohan; Tiwari, Sagendra (Scientific World, 2010)
Nepal's wetlands are recognized critical habitats for several rare and endangered flora and fauna. Wild rice is one of the wetland products. There are 4 species of wild rice, Oryza rufipogon; O. nivara, O. granulata and O. officinalis occurring in Nepal, of which 3 species, Oryza rufipogon; O. nivara and O. officinalis are wetlands dependent. Oryza rufipogon and O. nivara are considered as progenitors of Asian cultivated rice (O. sativa). Attempt is made to assess the status of wetlands and wild rice in Lumbini area, distributed in Rupandehi and Kapilvastu districts. Many wetland sites, the important habitats of wild rice are degrading and getting lost due to encroachment for conversion into rice fields, fishponds, extended settlements, and sedimentation. A number of wild rice locations are observed in private wetlands that are prone to conversion into rice fields and fishponds. Although, local communities use wild rice during religio-cultural ceremonies, they are not well aware about the values of wetlands and often consider wild rice as weeds. The government policy has also not given due importance to the conservation of wild rice. It is expected that many wild rice sites would be lost in a few years time. This paper discusses conservation needs of some of the wetland sites of Lumbini area such as Budhi Tal, Ajingara Tal, RangpurTal and Kale Khan Tal for the preservation of wild rice gene pool. Key words: Wetlands; Conservation; Wild rice; Lumbini area. DOI: 10.3126/sw.v5i5.2664 Scientific World, Vol. 5, No. 5, July 2007 95-99